Pengaruh Kompetensi Digital dan Motivasi Kerja terhadap Kinerja Karyawan SMPN 29 Bandung - Kamilia Aulia Nurnabilah; Deri Apriadi (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The digitalization era in the field of education requires educators and educational staff to possess competent digital capabilities and strong work motivation in achieving maximum work performance. This study was designed to analyze these factors on employee performance at SMPN 29 Bandung. The research methodology employed a quantitative correlational approach with survey techniques, involving the entire population of 59 participants through a total sampling approach. The data analysis process was conducted using SPSS version 25 software. The results showed that digital capabilities and work motivation had a significant impact on employee performance with a result of 52.2% (R² = 0.522). Individually, work motivation demonstrated a significant impact (t = 7.761; p = 0.000), while digital capabilities also showed a statistically significant influence (t = 1.980; p = 0.043). The findings of this study underscore the significance of combining psychological dimensions and technological expertise in supporting performance in the education sector, contributing to the development of human resource management theory, and presenting practical implications in formulating employee performance improvement strategies that are digitally and motivationally based. Therefore, performance improvement cannot rely solely on technological capabilities, but must be accompanied by strengthening internal employee motivation through adaptive and sustainable managerial strategies.